Enhancing Financial Literacy of STIKes Bina Insani Sakti Students through Educational Synergy with OJK Towards a Financially Smart Jambi - Surya, Tiara Lilis; Lestari, Anggia Ayu (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Financial literacy is an essential competency for the younger generation in facing the challenges of the modern economy. Unfortunately, the level of financial literacy in Indonesia remains relatively low, including among university students. This community service program aims to enhance the financial literacy knowledge and skills of students at STIKes Bina Insani Sakti through educational synergy with the Financial Services Authority (OJK) of Jambi Province. The event was held on May 27, 2025, in the form of a socialization session using an interactive lecture approach, complemented by pre-test and post-test evaluations. The topics covered included personal financial management, the dangers of illegal online loans and online gambling, investment principles, and an introduction to capital market instruments. The pre-test results indicated that the participants' initial understanding was low, but after the educational intervention, there was a significant improvement, particularly in financial management and risk understanding. The post-test results showed an average improvement of 12% across all tested aspects. This program demonstrates that a collaborative approach between educational institutions and financial regulators is effective in enhancing students' financial literacy. In the future, similar activities are expected to reach a wider target audience and enrich educational content to create a financially literate society in Jambi.